Mapping the Evolution of IBD Treatment: A Bibliometric Study on Biologics and Small Molecules - Huibo Li; Jia Wang; Yang Hu; Wei Hu; Jun Li; Yang Liu; Rongsheng Zhao; Yi Zhun Zhu (Pharmaceuticals)
Objectives: This bibliometric analysis investigates recent research trends in biologics and small molecules for treating inflammatory bowel disease (IBD) based on literature from the past decade. Methods: This cross-sectional study involved analyzing data retrieved from the Web of Science Core Collection (WoSCC) database to examine the evolution and thematic trends of biological agents and small-molecular drugs for IBD conducted between 1 January 2014, and 20 September 2024. VOSviewer software was utilized to assess co-authorship, co-occurrence, co-citation, and network visualization, followed by a further discussion on significant sub-themes. Results: From 2014 to 20 September 2024, the annual number of global publications increased by 23%, reflecting an acceleration in research activity. The journal “Inflammatory Bowel Diseases” published the highest number of manuscripts (579 publications) and garnered the most citations (13,632 citations), followed by the “Journal of Crohn’s & Colitis” (480 publications) and “Alimentary Pharmacology & Therapeutics” (250 publications). The United States led in productivity with 1943 publications and 66,320 citations, with UC San Diego (291) and authors Sandborn and Vermeire (180) topping the list. The co-occurrence cluster analysis of the top 100 keywords resulted in the formation of six distinct clusters: Disease Mechanisms, Drug Development, Surgical Interventions, Therapeutic Drug Monitoring (TDM), Immunological Targets, and Emerging Therapies. Burst terms (TNF-α inhibitors, JAK inhibitors, and trough-level optimization) highlight trends toward personalized biologics and small-molecule regimens. Conclusions: The bibliometric analysis indicates that IBD therapeutic research and clinical applications focus on biologics and small molecules, with research trends leaning toward precise therapy conversion or the combination in non-responders. Future work will assess monotherapy, the combination, and conversion therapies and investigate new drugs targeting inflammatory pathways.